Optical spectroscopy of low-dimensional quantum spin systems - Schmidt, Kai Phillip; et al. (2003)
Low-dimensional quantum spin systems display fascinating excitation spectra. In recent years, optical spectroscopy was shown to be a powerful tool for the study of these spectra by means of phonon-assisted infrared absorption. We discuss the results of antiferromagnetic S=1/2 cuprates with various topologies: the spinon continuum observed in the weakly coupled chains of CaCu2O3, two-triplet bound states and the continuum of the two-leg ladders in (La,Ca)(14)Cu24O41, and the bimagnon-plus-phonon spectrum of the bilayer YBa2Cu3O6, an undoped parent compound of the 2D high-T-c cuprates. Various theoretical approaches (dynamical DMRG, continuous unitary transformations (CUT), and spin-wave theory) are used for a quantitative analysis. Particular attention is paid to the role of the cyclic four-spin exchange.